Towards polyvalent ion batteries: A zinc-ion battery based on NASICON structured Na3V2(PO4)3. (July 2016) - Li, Guolong; Yang, Ze; Jiang, Yan; Jin, Chuanhong; Huang, Wei; Ding, Xuli; Huang, Yunhui
Abstract: Zinc-ion batteries are considered as potential large-scale renewable energy storage devices due to low redox potential, low cost, large capacity, high electric conductivity, nontoxicity and easy processing of zinc metal. However, the development of cathode materials for zinc-ion batteries to date has been mainly limited to tunnel manganese oxides and Prussian blue analogues. Here we have firstly developed NASICON structured Na3 V2 (PO4 )3 as cathode material for Zn-ion batteries. To compensate the low conductivity, graphene-like carbon wrapped Na3 V2 (PO4 )3 nanoparticles are fabricated. With Na3 V2 (PO4 )3 /C as cathode, Zn metal as both counter and reference electrodes, and 0.5 mol L −1 Zn(CH3 COO)2 solution as electrolyte, the aqueous Zn-ion battery delivers a reversible capacity of 97 mA h g −1 at 0.5 C and retains 74% capacity after 100 cycles. Meanwhile, the battery can be charged and discharged at high rate up to 10 C. The cyclic voltammogram analysis shows that the Zn-ion storage in Na3 V2 (PO4 )3 is a diffusion-controlled kinetic process. A mechanism of Zn ion occupancy variation during cycling is proposed. Our results provide an example for understanding and designing the intercalation process of divalent metal ions in NASICON structured cathode for new type rechargeable divalent metal ion batteries. Graphical abstract: Highlights: NASICON-structured Na3 V2 (PO4 )3 is firstly reported to storage divalent metal ions. Rechargeable aqueous Zn-ion battery with Na3 V2 (PO4 )3 as cathode is developed. Excellent Zn-ion storage performance is attained in carbon-wrapped Na3 V2 (PO4 )3 nanoparticles. A mechanism of Zn ion occupancy variation in Na3 V2 (PO4 )3 during cycling is proposed.